2014
DOI: 10.1177/0893318913513270
|View full text |Cite
|
Sign up to set email alerts
|

Appropriating the Words of Strategy in Performance Appraisal Interviews

Abstract: This study examines strategy as situated discourse in performance appraisal interviews. Based on illustrative video-recorded data, our findings show how strategy is appropriated in face-to-face interaction between managers and employees who engage in evoking the pragmatic and functional meanings of strategy concepts and discourse. The study specifically highlights the embodied, intertextual, and material nature of strategy; how people use gestures to make the strategy more concrete and complete; how appropriat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 60 publications
1
20
0
Order By: Relevance
“…The extent of its application in management suggest that the gap may act as an ontological metaphor (Lakoff and Johnson, 1980), that is, managers orient themselves to the challenge of strategy implementation as they would toward a real, physical gap (failing to cross it would cause one to fall; building a bridge allows one to cross the gap). This is consistent with studies on material expressions of strategy such as PowerPoint slides (Kaplan, 2011) and narrative plans (Sorsa et al, 2014;Vaara, Sorsa, and Pälli, 2010), which have shown that material expressions are, on the one hand, malleable as they are edited during the strategy process, and directive, on the other hand, as they do influence action (Jarzabkowski and Kaplan, 2015;Kaplan, 2011;Vaara et al, 2010).…”
Section: Patterning: Discovering "Top-down" and "Bottom-up Bridging"supporting
confidence: 87%
See 1 more Smart Citation
“…The extent of its application in management suggest that the gap may act as an ontological metaphor (Lakoff and Johnson, 1980), that is, managers orient themselves to the challenge of strategy implementation as they would toward a real, physical gap (failing to cross it would cause one to fall; building a bridge allows one to cross the gap). This is consistent with studies on material expressions of strategy such as PowerPoint slides (Kaplan, 2011) and narrative plans (Sorsa et al, 2014;Vaara, Sorsa, and Pälli, 2010), which have shown that material expressions are, on the one hand, malleable as they are edited during the strategy process, and directive, on the other hand, as they do influence action (Jarzabkowski and Kaplan, 2015;Kaplan, 2011;Vaara et al, 2010).…”
Section: Patterning: Discovering "Top-down" and "Bottom-up Bridging"supporting
confidence: 87%
“…Yet, strategy scholars do not yet use video-based methods as standard tools of their trade. With a few exceptions (Liu and Maitlis, 2014;Sorsa, Pälli, and Mikkola, 2014), published video-based work is almost nonexistent in our field. Video cameras are cheap and readily available even in cell phones.…”
Section: Introductionmentioning
confidence: 99%
“…Analyzing how the plenum of agencies (Cooren, 2006) participates in constituting organizational activities involves focusing on "how people implicitly or explicitly keep invoking, evoking, and convoking various forms of agency in their conversations" (Cooren, 2015: 477). Although recognizing the presence of various agents in communication, the CCO perspective studies communication with a linguistic focus, paying less attention to the material and aesthetic properties of experience and their communicative possibilities (Sorsa, Pälli & Mikkola, 2014). In this context, examining music as embodied communication provides a useful transition.…”
Section: Materially Mediated Communication: Aesthetics and Ccomentioning
confidence: 99%
“…In order to study aspects of performance, the concept of 'footing' (Goffman, 1981b;Mueller & Whittle, 2011;Sorsa et al, 2014) can be helpful: footing refers to the technique, not necessarily conscious, where a speaker only animates what she says, thus essentially speaks on behalf of someone else, who as author wrote the words, and/or as principal represents the position or values on whose behalf the animator speaks. 'In our last board meeting, the CEO has made it clear that he wants this change.…”
Section: Footingmentioning
confidence: 99%